(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article examines the pragmatic features of the lexeme "halollik" (honesty) in the Uzbek language from the perspective of cognitive linguistics. The study considers "honesty" not only as an ethical concept but also as a pragmatic tool expressing communicative intention, evaluative position, and social norms in discourse. The analysis focuses on the relationship between the lexeme and speech acts, implicature, evaluative pragmatics, discursive functions, and cultural cognitive models. Particular attention is paid to how pragmatic meanings associated with "honesty" are realized in different communicative contexts. The findings demonstrate that the lexeme possesses strong pragmatic potential and reflects culturally embedded cognitive and social values in the Uzbek linguistic consciousness.